2012
DOI: 10.1353/rhe.2012.0037
|View full text |Cite
|
Sign up to set email alerts
|

Mentors and College Student Leadership Outcomes: The Importance of Position and Process

Abstract: Mentorship is empirically related to several desired outcomes in college students including academic success and career development. Yet little is known about how mentorship aids leadership development in college students. This study uses data from the Multi-Institutional Study of Leadership, a national study with more than 110,000 participants from 101 institutions, to explore this issue. Findings show that leadership capacity is influenced by the mentorship process and the type of mentor (faculty, staff, emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(133 citation statements)
references
References 66 publications
6
125
0
2
Order By: Relevance
“…The reviewed research extends prior knowledge regarding potential benefits of mentoring for both the protégé (student) and mentor (Amaral & Vala, 2009;Campbell, Smith, Dugan, & Komives, 2012), sensemaking of the mentoring relationship and associated experiences (Griffin, 2013;Luna & Prieto, 2009), and mentoring as related to civic outcomes such as social responsibility and socially responsive leadership (Haddock et al, 2013). Qualitative findings also add to knowledge regarding the mentee and mentor matching process, students' and mentors' expectations for mentoring relationships, and what mentoring looks like in the context of particular disciplines and programs.…”
Section: Synthesis Of Key Findingsmentioning
confidence: 66%
See 2 more Smart Citations
“…The reviewed research extends prior knowledge regarding potential benefits of mentoring for both the protégé (student) and mentor (Amaral & Vala, 2009;Campbell, Smith, Dugan, & Komives, 2012), sensemaking of the mentoring relationship and associated experiences (Griffin, 2013;Luna & Prieto, 2009), and mentoring as related to civic outcomes such as social responsibility and socially responsive leadership (Haddock et al, 2013). Qualitative findings also add to knowledge regarding the mentee and mentor matching process, students' and mentors' expectations for mentoring relationships, and what mentoring looks like in the context of particular disciplines and programs.…”
Section: Synthesis Of Key Findingsmentioning
confidence: 66%
“…Grounded by the social change model of leadership development (Higher Education Research Institute, 1996), the researchers found that both faculty and peer mentoring relationships predicted measures of socially responsive leadership. Similarly, findings by Campbell et al (2012) suggest that mentoring is positively related to students' leadership capacity. Results also suggest that students who have faculty mentors may benefit more from mentoring when compared to students who are mentored by student affairs mentors.…”
Section: College Adjustment and Developmentmentioning
confidence: 89%
See 1 more Smart Citation
“…Many higher education organizations worldwide are developing peer mentoring relationships. A broad diversity of models for mentoring in these settings has been studied and the benefits of mentoring are confirmed by many authors (Allen, Russell, & Maetzke, 1997;Campbell, Smith, Dugan, & Komives, 2012;Colvin & Ashman, 2010;Dawson, 2014;Fleck & Mullins, 2012;Fox & Stevenson, 2004;Goff, 2011;Hall, & Jaugietis, 2011;Heirdsfield et al, 2008;Holt & Berwise, 2012;Horowitz & Christopher, 2012;Hryciw, Tangalakis, Supple, & Best, 2013;Lynn, 2010;Reddick, Griffin, Cherwitc, Cerda-Prazak, & Bunch, 2012;Reyes, 2012;T. Smith, 2008;D.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Willis, Bland, Manka, and Craft (2012) investigated peer mentoring in an educational setting and confirmed social skills were developed through positive mentoring experiences. Further to the concept of leadership capacity enhancement for mentors in higher education settings, Campbell et al (2012) supported mentoring as a key influence on leadership development in American college settings, with an emphasis on the development of leadership skills amongst the protégés in the relationship. In a study by Harris (2013), data on students' perceptions of mentoring relationships in a higher education setting clustered into the general categories of "personal support, professional development, and role modelling" (p. 87).…”
Section: Literature Reviewmentioning
confidence: 99%